2016
DOI: 10.1016/j.supflu.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Visual and in situ Raman spectroscopic observations of the liquid–liquid immiscibility in aqueous uranyl sulfate solutions at temperatures up to 420°C

Abstract: spectroscopic observations of the liquid-liquid immiscibility in aqueous uranyl sulfate solutions at temperatures up to 420 circ C, The Journal of Supercritical Fluids http://dx.doi.org/10. 1016/j.supflu.2016.03.005 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…A related consideration is the reported occurrence of liquid-liquid immiscibility observed in multiple sulfate-bearing systems (e.g. UO 2 , Li, Mg 2830 ) at elevated temperatures (>285.8 °C, >336.5 °C, and >259.5 °C, respectively) 31 , which may serve to provide a source of excess sulfate for complexation. In these studies, aqueous sulfate solutions were observed to separate into a high density, sulfate-rich (up to 70% of total sulfate) phase and a low-density sulfate-depleted aqueous phase.…”
Section: Discussionmentioning
confidence: 99%
“…A related consideration is the reported occurrence of liquid-liquid immiscibility observed in multiple sulfate-bearing systems (e.g. UO 2 , Li, Mg 2830 ) at elevated temperatures (>285.8 °C, >336.5 °C, and >259.5 °C, respectively) 31 , which may serve to provide a source of excess sulfate for complexation. In these studies, aqueous sulfate solutions were observed to separate into a high density, sulfate-rich (up to 70% of total sulfate) phase and a low-density sulfate-depleted aqueous phase.…”
Section: Discussionmentioning
confidence: 99%
“…23,76,77 The slight temperature dependence of ṽ1(UO 2 2+ ) is consistent with the only other hightemperature Raman studies in the literature. 28,78 Extrapolation of the band position of UO 2 2+ (aq) up to 375 °C using the welldefined linear behavior of the O−U−O vibrational stretch from 25 to 300 °C was assumed to result in minimal error.…”
Section: Computational Methods: Density Functional Theorymentioning
confidence: 99%
“…The value of the scattering coefficient of UO 2 2+ (aq) relative to CF 3 SO 3 − (aq) varied little with temperature, and the use of the average value of 2.43 ± 0.06 over all temperatures introduces negligible uncertainty, especially at high temperatures where UO 2 2+ (aq) is either a minor species or undetectable in solution. 28 4.2. Raman Spectra and Scattering Coefficients of UO 2 SO 4 0 (aq) and UO 2 (SO 4 ) 2 2− (aq).…”
Section: Computational Methods: Density Functional Theorymentioning
confidence: 99%
See 2 more Smart Citations